Research on Effect of Structured Dental Hygiene Education on Maternal Knowledge of Under-Five Care - Hemlata, Sankalp; Jagotra, Manisha (Journal of Educational Research and Policies, 2025)
The aim of the study was to assess the effect of structured teaching programme on knowledge of mothers regarding dental hygiene of under five children. The objectives of the study were to assess the knowledge of mothers regarding dental hygiene of under five children, determine the effect of structured teaching programme on knowledge of mothers regarding dental hygiene of under-five children, find out the association between level of knowledge of mothers regarding dental hygiene of under-five children and selected socio demographic variables. The researcher adopted quantitative pre experimental one group pretest posttest design for the study. Sixty mothers who have under-five children attending the paediatric OP clinics of SSNMM Hospital, Varkala were selected using convenience sampling technique. Data collection tools were structured questionnaires to collect socio demographic variables and to assess the knowledge of mothers regarding dental hygiene of under-five children. Pretest was done to assess the level of knowledge of mothers regarding dental hygiene of under-five children and structured teaching programme was administered on the same day. Posttest was conducted four weeks after the intervention. The effect of the structured teaching programme on knowledge of mothers regarding dental hygiene of under-five children was computed by ‘t’ test (t= 22.15, P<0.001). Association between the level of knowledge of mothers and selected socio demographic variables were also assessed. There was statistically significant association between level of knowledge of mothers and selected socio demographic variables like occupation and education of mothers. There was statistically no significant association between level of knowledge of mothers and selected socio demographic variables like age, income, residence, type of family, religion and number of children (P>0.05).